The Effectiveness of GTA V Roleplay in Enhancing Online Players’ Speaking Skills: A Study on the Executive Server of Discord “Warung Bu Erte” (Journal of Emerging Technology in Teaching and Learning (JETTLe), 2025)
This study investigates the effectiveness of Grand Theft Auto V (GTA V) roleplay in improving the speaking skills of online players within the Executive Server of Discord “Warung Bu Erte.” The research was motivated by the increasing use of online gaming platforms as informal learning environments, where interaction and communication are essential for gameplay. Using a quasi-experimental design, data were collected from participants actively engaged in immersive roleplay activities, with pre-tests and post-tests administered to measure speaking performance. The findings indicate that participation in roleplay significantly enhanced players’ fluency, vocabulary use, and confidence in speaking English. The results suggest that online roleplay can function as an innovative medium for language learning, offering authentic contexts for communication, collaboration, and meaning negotiation. This study contributes to the growing body of research on game-based learning, highlighting the potential of digital platforms to support second language acquisition.